Formation of discursive competence of future foreign language teachers in conditions of professionally oriented communication - Kabden, N.M.; Niyazova, A.Y. (Karagandy University of the name of acad. E.A. Buketov, 2025)
The article examines the formation of discursive competence in future foreign language teachers for professionally oriented communication. Discursive competence is crucial for educators, enabling effective speech functions and professional communication skills. This facilitates the effective development of communication skills in a professional context. Discourse competence has distinct features: it is cohesive, coherent, and consistent, relying on structural relationships that break a whole into smaller components. The study aims to identify the influence of professionally oriented communication on the formation of discursive competence in future foreign language teachers. The object of the study is the discursive competencies of future foreign language teachers. The research methodology was based on practical testing of developed methods, conducting sociological surveys, and confirming hypotheses using the non-parametric Mann-Whitney statistical criterion. The experiment’s results were evaluated using comparison, analysis, synthesis, and theoretical generalization. The control stage of the pedagogical experiment demonstrated significant differences, which may indicate that the tested method can indeed be considered effective and capable of developing discursive competencies through the application of professionally oriented communications in the training of future foreign language teachers. Therefore, the implementation of innovative approaches and the adaptation of teaching methods to the real needs of students are deemed essential conditions for preparing qualified specialists in the field of foreign language teaching.
Кәсіби бағдарланған қарым-қатынас жағдайында болашақ шет тілі мұғалімдерінің дискурсивті құзыреттілігін қалыптастыру
Формирование дискурсивной компетентности будущих учителей иностранного языка в условиях профессионально-ориентированного общения
Keywords: discourse; competencies; discourse competencies; learning process; professionally oriented communication; communication; linguistics; foreign language; teacher; university